5, 7-Dihydroxy-4′-methoxyisoflavone induces apoptosis by inhibiting the ERK and Akt pathways in human osteosarcoma cells. (February 2015) - Lu, Xiaosheng; Zhao, Jinmin; Li, Tingyang; Huang, Meijing; Liang, Jian; Wei, Wen
Abstract Phytoestrogens are known to prevent tumor progression by inhibiting proliferation and inducing apoptosis in cancer cells. In this study we determine the effect of 5, 7-dihydroxy-4′-methoxyisoflavone, a phytoestrogen, on proliferation and apoptosis in the human osteosarcoma (OS) cell line U2OS. 5, 7-Dihydroxy-4′-methoxyisoflavone dose-dependently inhibited proliferation in U2OS cells, which was accompanied by an increase of early apoptotic cells. However, 5, 7-dihydroxy-4′-methoxyisoflavone had little effect on the growth and apoptosis of normal human skin fibroblast (HSF) cells. This may indicate that 5, 7-dihydroxy-4′-methoxyisoflavone can selectively inhibit the proliferation of cancerous cells. Meanwhile, 5, 7-dihydroxy-4′-methoxyisoflavone decreased the protein levels of phosphorylated ERK and Akt. Inactivation of these pathways was confirmed by upregulation of Bax expression and downregulation of Bcl-2 expression. Phosphorylated Akt protein levels were decreased in HSF cells only at a high concentration (80 μM) of 5, 7-dihydroxy-4′-methoxyisoflavone. Together, we suggest that 5, 7-dihydroxy-4′-methoxyisoflavone promotes cell death of human OS cells U2OS by induction of apoptosis, which is associated with the inhibition of ERK and Akt signaling. Thus, 5, 7-dihydroxy-4′-methoxyisoflavone may have less toxicity compared to normal tissue and could be a potential therapy for OS.